Evolución histórica del concepto de justo precio y de la rescisión por "laesio ultradimidium" - Valmaña Valmaña, Silvia (Revista de Derecho de la UNED (RDUNED), 2015)
La noción latina de iustum pretium, surgiría en el Derecho romano postclásico, a través de las Constituciones de Diocleciano y Maximiano CJ.4,44,2 y CJ.4,44,8, que darían origen a la rescisión del contrato de compraventa por laesio ultradimidium. En la etapa clásica, regía el criterio de la voluntad contractual de las partes para la determinación del precio, y únicamente se exigía que el precio fuese cierto, determinado, real y verdadero. El concepto de iustum pretium evoluciona históricamente, en el Derecho canónico, Fuero Real, las Partidas, Costumbres de Tortosa, el Ordenamiento de Alcalá y la Novísima Recopilación, quedando excluido del Código Civil vigente al suprimir el Proyecto del Código Civil de 1851 la rescisión por laesio ultradimidium. Solamente, la Compilación del Derecho Civil de Cataluña y el Fuero Nuevo de Navarra reconocen la rescisión por lesión, y aplican, respectivamente, el valor en venta y valor de la prestación, que se identifican con el justo precio, para determinar la existencia de lesión. La jurisprudencia del Tribunal Supremo no exige que el precio sea justo, sino que sea cierto, y que pueda determinarse con referencia a otra cosa cierta, o al arbitrio de persona determinada, sin necesidad de que se fije cuantitativamente en el momento de la celebración del contrato. The Latin concept of iustum pretium first appeared in post-classical Roman Law in the Constitutions CJ.4.44.2 and CJ.4.44.8 of Diocletian and Maximian. These laid down the possibility of the rescission of contracts of sale due to laesio ultradimidium. Previously, during the classical period, the pricing criteria had been merely based on the willingness of the parts involved to determine a price between themselves with the only requirement being that the price be settled, definite, real and true. The concept of iustum pretium evolves historically through Canon Law, the Fuero Real (Royal decrees drawn up by Alfonso X in the 13th century), las Partidas (a seven-part legal code laid down by Alfonso X), the Costumbres de Tortosa (a legal body of work compiled in the late 13th century), the Ordenamiento de Alcalá (a collection of laws enacted by Alfonso XI in the 14th century) and the Novísima Recopilación (1805 compilation of laws). This notion of contract rescission due to laesio ultradimidium is not included in the current Civil Code as it was removed in the 1851 Civil Code project. Nowadays, only the Catalan Civil Rights Compilation and the Fuero Nuevo laws of Navarra recognize contract rescission due to legal lesion and apply, respectively, the market value and real value, identified with the just price, to determine the existence of said lesion. The jurisprudence of the Spanish Supreme Court does not require the price to be just, but to be settled. This price can be determined either through comparison to another certain price or at the discretion of the person in question without the need to quantify it at the time of drawing up the contract.